2013
DOI: 10.1007/s12262-013-0906-4
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Controlled Trial of Day-Case Laparoscopic Cholecystectomy vs Routine Laparoscopic Cholecystectomy

Abstract: Many randomised controlled trials conducted worldwide favours for day-case laparoscopic cholecystectomy, but questions have been raised regarding its application in developing country like ours. Hence, considering it a high time to review current practices, we conducted this trial to report our experience with day-case laparoscopic cholecystectomy and to access its feasibility and safety in our set-up. Data from 65 patients with symptomatic gallstone were randomised to perform laparoscopic cholecystectomy eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Postoperative Complications. Postoperative complications were reported in seven trials [32,33,[35][36][37][38][39] with 287 patients in the day surgery group and 294 patients in the inpatient group. In total, 15 out of 287 (5.2%) participants had postoperative complications in the day surgery group compared with 21 out of 294 (7.1%) in the inpatient group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Postoperative Complications. Postoperative complications were reported in seven trials [32,33,[35][36][37][38][39] with 287 patients in the day surgery group and 294 patients in the inpatient group. In total, 15 out of 287 (5.2%) participants had postoperative complications in the day surgery group compared with 21 out of 294 (7.1%) in the inpatient group.…”
Section: Discussionmentioning
confidence: 99%
“…There were 10 studies [32][33][34][35][36][37][38][39] that compared the LC in the day surgery unit versus inpatient unit, and 2 of them [18,26] were retrospective controlled studies which were excluded from quantitative synthesis. Of the remaining 8 RCTs, there were 301 patients that underwent LC in day surgery units and 308 patients underwent LC in the inpatient units.…”
Section: Baseline Characteristics the Eligible 24 Studies Includingmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the admission rate was slightly high (11.76%) however the readmission (0.36%) rate was low. [21] Some reports demonstrated the safety of DSLC in older and high-risk patients (ASA grade III) while, others have concluded that a previous diagnosis of acute cholecystitis, acute biliary pancreatitis, and ASA >II were highly predictive of a hospital admission. [22][23][24] In our study, no patients with ASA grade more than II were included.…”
Section: Discussionmentioning
confidence: 99%